Pengembangan Pariwisata dengan Community Based Tourism di Desa Wisata Penatih Denpasar - Sutama, I Kompyang Gede Sutama; Nyoman Diah Utari Dewi; Luh Riniti Rahayu (Jurnal Studi Perhotelan dan Pariwisata, 2023)
Purpose: Through the development of community-based tourism (CBT), it is hoped that the tourism industry can become an instrument of development that is more prosperous for the community around tourist objects in Penatih Village because of its tourism potential. Methodology: We used qualitative research methods and descriptive approaches with primary and secondary data and a SWOT analysis. Results: The results show that the trainer tourism village has beautiful natural tourism potential that can be developed into a leading tourist destination in Denpasar. Efforts that can be made in its development involve the community directly as tourism activists, better known as community-based tourism (CBT). Strategies to improve leading tourist villages include implementing community-based tourism (CBT) as a tourism development approach, politically empowering communities, establishing cooperation, and forming tourism awareness groups. Penatih Tourism Village has a sustainable subak program that is also a conservation effort to restrain land conversion and provide local community productivity. In addition, it needs to be supported by infrastructure so that Subak can be productive and sustainable. The development of the Penatih Tourism Village with the Subak sustainable icon is the spirit of the development of this village so that development can be carried out holistically and sustainably.